Evidence for an extinct lineage of angiosperms from the Early Cretaceous of Patagonia and implications for the early radiation of flowering plants. Issue 1 (10th June 2020) - Coiro, Mario; Martínez, Leandro C.A.; Upchurch, Garland R.; Doyle, James A.
Summary: The pinnately lobed Aptian leaf fossil Mesodescolea plicata was originally described as a cycad, but new evidence from cuticle structure suggests that it is an angiosperm. Here we document the morphology and cuticle anatomy of Mesodescolea and explore its significance for early angiosperm evolution. We observed macrofossils and cuticles of Mesodescolea with light, scanning electron and transmission electron microscopy, and used phylogenetic methods to test its relationships among extant angiosperms. Mesodescolea has chloranthoid teeth and tertiary veins forming elongate areoles. Its cuticular morphology and ultrastructure reject cycadalean affinities, whereas its guard cell shape and stomatal ledges are angiospermous. It shares variable stomatal complexes and epidermal oil cells with angiosperm leaves from the lower Potomac Group. Phylogenetic analyses and hypothesis testing support its placement within the basal ANITA grade, most likely in Austrobaileyales, but it diverges markedly in leaf form and venation. Although many Early Cretaceous angiosperms fall within the morphological range of extant taxa, Mesodescolea reveals unexpected early morphological and ecophysiological trends. Its similarity to other Early Cretaceous lobate leaves, many identified previously as eudicots but in some cases pre‐dating the appearance of tricolpate pollen, may indicate that Mesodescolea is part of a larger extinct lineage of angiosperms.